2022
DOI: 10.3390/biomedicines10071463
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignancy in Patients with Asthma-COPD Overlap Compared to Patients with COPD without Asthma

Abstract: Chronic inflammation such as asthma may lead to higher risks of malignancy, which may be inhibited by anti-inflammatory medicine such as inhaled corticosteroids (ICS). The aim of this study was to evaluate if patients with asthma-Chronic Obstructive Pulmonary Disease (COPD) overlap have a higher risk of malignancy than patients with COPD without asthma, and, secondarily, if inhaled corticosteroids modify such a risk in a nationwide multi-center retrospective cohort study of Danish COPD-outpatients with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Their risk for any cancer diagnosis was evaluated within the following two years. Results showed that there was no association between asthma-COPD overlap and cancer, and that ICS use did not seem to modify the risk for malignancy [9].…”
Section: Cancer Risk In Patients With Asthma-copd Overlapmentioning
confidence: 90%
See 1 more Smart Citation
“…Their risk for any cancer diagnosis was evaluated within the following two years. Results showed that there was no association between asthma-COPD overlap and cancer, and that ICS use did not seem to modify the risk for malignancy [9].…”
Section: Cancer Risk In Patients With Asthma-copd Overlapmentioning
confidence: 90%
“…B onnesen et al . [ 9 ] (Copenhagen, Denmark) aimed to determine whether asthma was associated with an increased risk of cancer among COPD patients and the role of ICS as anti-inflammatory agents. A total of 50 897 COPD patients from Danish registries were included in the study and separated into two groups: COPD without asthma, and COPD with concomitant asthma (based on the diagnosis of a respiratory medicine physician).…”
Section: Group 101: Clinical Problemsmentioning
confidence: 99%
“…Non-communicable diseases (NCDs) have a significant impact on global mortality, with CNCRDs like asthma and COPD being major contributors. In high-risk occupations like mining and construction, respiratory conditions are common, leading to a considerable number of deaths (10). Workers in the pharmaceutical industry may be exposed to substances that can affect their respiratory health, leading to allergies and sensitization to certain chemicals (11).…”
Section: Introductionmentioning
confidence: 99%
“…This inflammation may induce a prothrombotic stage causing an increased risk of cardiovascular disease seen in patients with asthma [6][7][8][9][10][11]. An asthma-inflammation driven increased risk of cancer has also been proposed [12].…”
Section: Introductionmentioning
confidence: 99%
“…This inflammation may induce a prothrombotic stage causing an increased risk of cardiovascular disease seen in patients with asthma [ 6 11 ]. An asthma-inflammation-driven increased risk of cancer has also been proposed [ 12 ]. Randomised clinical trials have even shown that inhibition of interleukin-1β by canakinumab [ 13 ] and of tubulin by colchicine [ 14 ] reduces the risk of ischaemic heart disease, thus proving that low-grade inflammation plays a causative role in the development of ischaemic heart disease and its events.…”
Section: Introductionmentioning
confidence: 99%